De Mariemont à Hanoi : conservation et restauration des céramiques d’Extrême Asie - Catherine Noppe (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The paper describes the unavoidable differences in conception and practices in conservation-restoration of Asiatic ceramics conserved on one hand in the Royal Museum of Mariemont and on the other in Vietnam museums. It mentions the fruitful collaborations established amongst other in the frame of a scientific mission to Hanoi.